Determinan Kinerja UMKM Sektor Kuliner di Kecamatan Pekanbaru Kota - Supriadi; Siti Rodiah; Linda Hetri Suriyanti (Juara: Jurnal Riset Akuntansi, 2022)
This study aims to examine the effect of financial literacy, government policies and innovation on the performance of MSMEs in the culinary sector in Pekanbaru Kota sub-district. This study used a sample of 67 SMEs which were determined based on the purpose sampling method. The analytical method used was multiple regression analysis using the SPSS version 21 program. The results of this study show that innovation has a significant impact on MSME performance, but financial literacy and government policies have no significant effect on the performance of MSMEs in Pekanbaru Kota District.